2019
DOI: 10.1016/j.envpol.2019.01.129
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood pressure associated with lead, manganese, and selenium in a Bangladeshi cohort

Abstract: Background: Heavy metal contamination is widespread in Bangladesh. Previous studies have observed lead increases blood pressure over time. However, the role of other metal contaminants and essential micronutrients, which could also adversely affect blood pressure or act as protective factors, is understudied. Objectives:We therefore evaluated the associations of lead, manganese, and selenium with blood and pulse pressure trajectories. Methods: We prospectively followed placebo-assigned participants nested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…It should also be noted that many previous studies did not examine (and thus may have missed) the possible nonlinear associations of these two elements with BP. Two recent studies, one in U.S. children (i.e., the Boston Birth Cohort) (Wang et al 2021) and one in Bangladeshi adults (Bulka et al 2019), reported nonlinear associations of Mn or Se with BP.…”
Section: Mn and Sementioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that many previous studies did not examine (and thus may have missed) the possible nonlinear associations of these two elements with BP. Two recent studies, one in U.S. children (i.e., the Boston Birth Cohort) (Wang et al 2021) and one in Bangladeshi adults (Bulka et al 2019), reported nonlinear associations of Mn or Se with BP.…”
Section: Mn and Sementioning
confidence: 99%
“…Selenium (Se) and manganese (Mn) are essential trace elements for human health. In adults, some studies suggested that Se and Mn may have protective effects against hypertension and CVD, although there is also evidence of possible adverse effects, nonlinear relationships, or null effects of these elements on BP and CVD (Bulka et al 2019;Laclaustra et al 2009; Lee and Kim 2011; Mordukhovich et al 2012;Nawrot et al 2007;Wu et al 2017). In pregnant women, we reported in the Boston Birth Cohort (Liu et al 2019) and in Project Viva (Liu et al 2020) that higher maternal Mn levels were prospectively associated with lower risk of preeclampsia, a pregnancy complication characterized by high BP and a known risk factor for child high BP (Zhang et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Results from epidemiological surveys and experimental studies indicate that toxic metal(loid)s such as arsenic (As), cadmium, and lead (Pb) can elevate blood pressure [15,16,17]. In addition, the relationship between the intake of essential trace elements and blood pressure has been widely studied at the population level; however, the dose-response relationships are complicated [18,19,20], due to challenges in maintaining blood pressure within a certain range. Likewise, the in uences of various metal(loid)s on blood vessel injuries depend on individual intake levels, as well as interaction effects among metal(loid)s. Generally, greater exposure to toxic metal(loid)s or disturbance in the balance of essential trace elements in the human body can lead to adverse effects on blood pressure stability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies based on NHANES [2011][2012] reported that levels of As, Pb, Cd and Hg in Asian population were higher than those in other racial/ethnic groups (including whites, blacks and Hispanics) in US [11,12]. In Asian countries, epidemiological studies have investigated the associations of As, Pb, Cd and Hg with blood pressure levels and risk of hypertension [13][14][15][16][17][18][19][20][21][22], but the results were inconsistent across these studies. In addition, the Asian Americans were consisted of Asian Indian (22.4%), Chinese (19.5%) and other Asians (58.2%) (Awata et al 2017b), which were quite different from the population included in previous studies performed in Asian countries.…”
Section: Introductionmentioning
confidence: 99%